Permeability prediction: core vs log-derived values - A. Kadir, A. Aziz; Hamid, M. Fauzi; Ikhan, Azman (1995)
Rock formation permeability is the most important parameter that indicates how efficient the reservoir fluid flow through the rock pores to the wellbore. Regardless of operations available downhole, its importance is reflected by the number available techniques (core measurement and well-log derivation) typically used to estimate it. Permeability estimates by individual techniques within the various permeability sources can vary with the state of rock (in-situ environment), fluid saturation distribution, flow direction, and the scaling of measurement. The paper reviews the available permeability-estimation techniques and discussed the important factors that illustrate their relationships. Usefulness of the relationship is demonstrated with field data.